Community‐acquired pneumonia among children: the latest evidence for an updated management - Cristiana M. Nascimento‐Carvalho (Brazilian Society of Pediatrics, 2020)
Objective: To provide cutting‐edge information for the management of community‐acquired pneumonia in children under 5 years, based on the latest evidence published in the literature. Data source: A comprehensive search was conducted in PubMed, by using the expressions: "community‐acquired pneumonia" AND "child" AND "etiology" OR "diagnosis" OR "severity" OR "antibiotic". All articles retrieved had the title and the abstract read, when the papers reporting the latest evidence on each subject were identified and downloaded for complete reading. Data synthesis: In the era of largely implemented bacterial conjugate vaccines and widespread use of amplification nucleic acid techniques, respiratory viruses have been identified as the most frequent causative agents of community‐acquired pneumonia in patients under 5 years. Hypoxemia (oxygen saturation ≤ 96%) and increased work of breathing are signs most associated with community‐acquired pneumonia. Wheezing detected on physical examination independently predicts viral infection and the negative predictive value (95% confidence interval) of normal chest X‐ray and serum procalcitonin < 0.25 ng/dL was 92% (77‐98%) and 93% (90‐99%), respectively. Inability to drink/feed, vomiting everything, convulsions, lower chest indrawing, central cyanosis, lethargy, nasal flaring, grunting, head nodding, and oxygen saturation < 90% are predictors of death and can be used as indicators for hospitalization. Moderate/large pleural effusions and multilobar infiltrates are predictors of severe disease. Orally administered amoxicillin is the first line outpatient treatment, while ampicillin, aqueous penicillin G, or amoxicillin (initiated initially by intravenous route) are the first line options to treat inpatients. Conclusions: Distinct aspects of childhood community‐acquired pneumonia have changed during the last three decades. Resumo: Objetivo: Fornecer informações de ponta para o manejo de crianças menores de cinco anos com pneumonia adquirida na comunidade, com base nas evidências mais recentes publicadas na literatura. Fonte de dados: Uma pesquisa abrangente foi feita no PubMed, com as expressões: "community‐acquired pneumonia" + "child" + "etiology" ou "diagnosis" ou "severity" ou "antibiotic". Todos os artigos encontrados tiveram o título e o resumo lidos e os artigos que relatavam as evidências mais recentes sobre cada assunto foram identificados e recuperados para leitura completa. Síntese dos dados: Na era das vacinas bacterianas conjugadas amplamente usadas e do uso difundido de técnicas de amplificação de ácidos nucléicos, os vírus respiratórios foram identificados como os agentes causadores mais frequentes de pneumonia adquirida na comunidade em pacientes com menos de cinco anos. A hipoxemia (saturação de oxigênio ≤ 96%) e o aumento do esforço respiratório são os sinais mais associados à pneumonia adquirida na comunidade. A sibilância detectada ao exame físico prediz de forma independente a infecção viral e o valor preditivo negativo (intervalo de confiança de 95%) da radiografia de tórax normal e a procalcitonina sérica < 0,25 ng/dL foi de 92% (77‐98%) e 93% (90‐99%), respectivamente. Incapacidade de beber e se alimentar, vomitar todo o alimento, convulsões, retração torácica subcostal, cianose central, letargia, aleteo nasal, estridor e saturação de oxigênio < 90% são preditores de óbito e podem ser usados como indicadores de hospitalização. Derrames pleurais moderados/grandes e infiltrados multilobulares são preditores de doença grave. A amoxicilina administrada por via oral é a opção de primeira linha para tratar pacientes ambulatoriais e a ampicilina ou penicilina cristalina G ou amoxicilina (administrada inicialmente por via intravenosa) são as opções de primeira linha para tratar pacientes hospitalizados. Conclusões: Aspectos distintos da pneumonia adquirida na comunidade durante a infância mudaram durante as últimas três décadas. Keywords: Child, Community‐acquired pneumonia, Diagnosis, Etiology, Treatment, Palavras‐chave: Criança, Pneumonia adquirida na comunidade, Diagnóstico, Etiologia, Tratamento